The course of retinal vasculitis. Issue 6 (7th February 2014) - Ali, Amro; Ku, Jennifer H; Suhler, Eric B; Choi, Dongseok; Rosenbaum, James T
Abstract : Aims: To determine if characteristics of retinal vasculitis correlate with ocular complications, or the response to different lines of treatment. Materials and methods: We performed a computerised database analysis of 56 patients evaluated for uveitis at the Casey Eye Institute from September 1985 until May 2010. All patients had non-infectious retinal vasculitis and at least 1 year of follow-up. Results: Although occlusive vasculitis was rare, retinal neovascularisation occurred much more commonly in the occlusive vasculitis subgroup than among the non-occlusive vasculitis subgroup (p<0.01). Epiretinal membrane (ERM) was found more commonly in the retinal vasculitis patients who presented with cotton wool spots and intraretinal haemorrhage compared to retinal vasculitis patients who presented with sheathing noted on clinical examination (p<0.01). Smoking was significantly related to vision loss. Age at presentation below 40 years correlated with therapy beyond oral corticosteroids Conclusions: The heterogeneity of retinal vasculitis should be considered in providing prognostic information. Neovascularisation occurs more commonly in occlusive retinal vasculitis, and ERM is diagnosed more frequently in conjunction with cotton wool spots and intraretinal haemorrhage rather than just vascular sheathing. Cigarette use predicts visual loss and patients who are relatively young often receive treatment beyond oral corticosteroids.